The use of artificial intelligence tools in scientific research: Reality and challenges – A survey study of postgraduate students at the International University of Africa (The International Journal of Educational Sciences and Arts, 2026)
The study aimed to identify the current status of graduate students’ use of artificial intelligence technologies at the International University of Africa in the preparation of scientific research, and to reveal the most prominent challenges faced by graduate students when using artificial intelligence technologies in conducting their scientific research. It also sought to analyze statistically significant differences in the level of graduate students’ utilization of artificial intelligence technologies in scientific research at the International University of Africa according to the variables of gender, academic specialization, and level of artificial intelligence use. The study adopted the descriptive survey method, and the study sample consisted of (32) male and female graduate students from the College of Education at the International University of Africa. The study found that graduate students are aware of the active role of artificial intelligence tools in improving the quality of scientific research, particularly in facilitating data collection and analysis, as this item achieved a high mean score (4.28). The results also showed a strong desire among students to develop their skills in using artificial intelligence in scientific research, as the statement expressing the desire to learn more obtained the highest mean score (4.41). In addition, artificial intelligence is used to a good extent in academic translation, analysis of scientific texts, and the generation of research ideas, indicating the diversity of areas in which these technologies can be beneficial within the research process.
Keywords: Artificial Intelligence; Scientific Research; Graduate Students